1974
DOI: 10.1088/0031-8949/10/1-2/008
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Spectrum of Gaseous AIF

Abstract: The results of a detailed rotational analysis involving the assignment of some 14 500 lines are reported. Observed bands have been ascribed to transitions between nine singlet states (including the ground state) and between seven triplet states. Singlet-triplet systems have not yet been observed, but the relative energies of the singlet and triplet states have been determined by the analysis of spin-forbidden perturbations. The ground state is π4σ2, X 1Σ+, and the first excited states π4σπ*, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…This data is suitable to get accurate information on the electronic potential curves and on the ro-vibrational energy level structure from which Franck-Condon factors can be calculated precisely. The fine and hyperfine structure, however, has barely been resolved [58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…This data is suitable to get accurate information on the electronic potential curves and on the ro-vibrational energy level structure from which Franck-Condon factors can be calculated precisely. The fine and hyperfine structure, however, has barely been resolved [58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…They reported without doubt that the bands of AlF are present in the umbral spectra. In addition to what precedes, this molecular system has been the subject of a number of experimental investigations since the early 1970 (See for example the papers by So and Richards (1974), Barrow et al (1974), Rosenwaks (1976, Huber and Herzberg (1979), Dyke et al (1984), Rogowski and Fontijn (1987), and Dearden et al (1991)). Some ab initio calculations aimed at characterizing the lower states of AlF have also been performed (Langhoff and Bauschlicher 1988;Rozas et al 1999, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Kopp and Barrow analysed the interaction of the A 1 state with the nearby b 3 + state and thereby determined the term energy of the triplet states relative to the singlet states [16]. A comprehensive study of the electronic states and the interaction between the singlet and triplet states followed [17]. In 1976, Rosenwaks et al observed the a 3 → X 1 + transition directly in emission [18] at the same time as Kopp et al did in absorption [19].…”
Section: Previous Workmentioning
confidence: 99%
“…The hyperfine structure of the rotational states in b 3 + was partly resolved and analysed by Barrow et al [17]. Their low-resolution spectra (typical linewidth of 0.05 cm −1 ) showed a triplet structure, which they ascribed to magnetic hyperfine effects of the 27 Al nucleus, whose nuclear spin is I Al = 5/2.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation